2007
DOI: 10.1177/1073191106298876
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Tibetan Translation of the Hopkins Symptom Checklist–25 and the Harvard Trauma Questionnaire

Abstract: This study sought to translate and validate the Hopkins Symptom Checklist-25 (HSCL) and the Harvard Trauma Questionnaire (HTQ) in a Tibetan population. Translated questionnaires were administered to 57 Tibetan survivors of torture/human rights abuses living in the United States and receiving services in a torture treatment program. Participants were evaluated to determine if they met criteria for major depressive episode, generalized anxiety disorder, or posttraumatic stress disorder (PTSD). Coefficient alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 16 publications
2
68
0
Order By: Relevance
“…As observed by many cross-cultural researchers (Crescenzi et al, 2002;Hollifield et al, 2002;Kagee & Naidoo, 2004), the validity of Western mental health constructs and standardized instruments is often unknown when applied to non-Western populations. Researchers have specifically questioned the construct of PTSD, and the HTQ as a measure of PTSD, in the Tibetan population (Holtz, 1998;Lhewa et al, 2007Terheggen et al, 2001. As in prior research, this study did not elicit or employ indigenous conceptualizations of mental illness.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As observed by many cross-cultural researchers (Crescenzi et al, 2002;Hollifield et al, 2002;Kagee & Naidoo, 2004), the validity of Western mental health constructs and standardized instruments is often unknown when applied to non-Western populations. Researchers have specifically questioned the construct of PTSD, and the HTQ as a measure of PTSD, in the Tibetan population (Holtz, 1998;Lhewa et al, 2007Terheggen et al, 2001. As in prior research, this study did not elicit or employ indigenous conceptualizations of mental illness.…”
Section: Discussionmentioning
confidence: 96%
“…Lhewa et al (2007) observed high internal consistency for both the anxiety and depression subscales (α = .89, .92, respectively), and strong diagnostic accuracy (compared to an independent psychiatric diagnosis) using the 1.75 cutoff score (sensitivity = .91, specificity = .88 for the anxiety subscale, and sensitivity = .89 and specificity = .87 for the depression subscale). Symptoms of PTSD were assessed with a Tibetan version of the Harvard Trauma Questionnaire (HTQ; Mollica et al, 1992), also developed by Lhewa et al (2007). The HTQ has demonstrated excellent statistical properties in a number of refugee studies (Hollifield et al, 2002;Renner, Salem, & Ottomeyer, 2006) and is considered the best-supported measure of PTSD for refugee populations (Hollifield et al, 2002).…”
Section: E T H O D Participantsmentioning
confidence: 90%
See 1 more Smart Citation
“…In another translation study of the HSCL-25 into the Dinka language for use with South Sudanese refugees, the authors found item 14 to be offensive to both men and women and recommended removal in order to be culturally sensitive to this population (Baird & Skariah, 2015). In a translation of the HSCL-25 into Tibetan, the authors discovered that sexual matters are not typically discussed in this culture; even when item 14 was removed, the depression subscale maintained consistency (Lhewa, Banu, Rosenfeld, & Keller, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Coefficient alpha of 10 first items HSCL-25 is 0.84 (Derogatis et al, 1974). HSCL-25 has high and accurate predictive level for both anxiety and depression symptoms or as psychological distress as general (Lhewa et al, 2007). Procedure.…”
Section: Instrument and Measurement Related Teachermentioning
confidence: 99%